Integrating HIV advanced disease management into a routine program setting: cohort from Mumbai, India - Shrikala Acharya; Ramesh Reddy Allam; Vijay Kumar Karanjkar; Dhirubhai Rathod; Prashant Deshpande; Amol Palkar; Shashikant Todmal; Sagar Koli; Sachin Dhande; Nalini Chava; Vijay V Yeldandi; Amit Harshana; et al. (BMC Health Services Research)
Abstract Background The advanced disease management (ADM) package, which aims to reduce morbidity and mortality in people with Advanced HIV disease (AHD, WHO stage III/IV and/or CD4 count < 200 cells/mm3 or age < 5 years), is not fully implemented in India. We assessed the feasibility of implementing the full WHO ADM package as part of routine HIV care under the programmatic setting in antiretroviral therapy centers of Mumbai. Methods We implemented the ADM package (screening, treatment, and prophylaxis for major opportunistic infections, rapid ART initiation, and ART adherence support) in 17 ART centers from October 2020 to December 2021. Treatment naïve and experienced persons with AHD, including children, were enrolled. We assessed the feasibility through coverage of ADM package components and reported the proportion of rapid ART initiation (≤ 7 days), cotrimoxazole prophylaxis, TB preventive treatment (TPT) for those eligible [(excluded active TB disease (n = 280) and those completed TPT prior to enrolment (n = 1,186)], TB-LAM screening (excluded current TB disease), and cryptococcal antigen (CrAg) assay (excluded children < 10 years of age). We used a point of care test for TB (LAM) and cryptococcus (CrAg) screening. We followed the prospective cohort for one year (through 31 July 2022) to document outcomes for survival and lost to follow- up (LTFU). Results We identified 4,334 PLHIV with AHD and provided the full ADM package to 64% (2,779/4,334); 297 did not receive ADM (146 died, 151 LTFU), and 1,258 received routine standard of care (587 had TB, 366 were at decentralized sites, and 305 LAM/CrAg kits were not available) with existing ART center staff. Nearly 78% (385/494) of treatment naïve were rapidly initiated on ART. Nearly 82% (1,129/1,383) and 99% (2,751/2,779) received TPT and cotrimoxazole prophylaxis, respectively. Of the eligible, 99% (2,508/2,524) and 98% (2,715/2,758) were screened for TB and cryptococcal infection, respectively. At the end of 12 months, 88% (2,458/2,779) were alive, 8% (210/2,779) died, and 4% (111/2,779) were LTFU. Mean survival time was significantly (p < 0.001) higher among treatment experienced people; 11.6 months (95% CI: 11.5,11.7) compared to treatment naïve people 10.8 months (95% CI: 10.5,11.0). Conclusion With careful anticipatory planning, stakeholder engagement, and training, implementing the full ADM package is feasible in a routine program setting with existing human resources. Additional intensive case management may be necessary for the reduction of mortality among treatment naïve PLHIV.